Meta-analysis of intermittent treatment with sulfadoxine-pyrimethamine in pregnancy in malaria endemic areas - Mkopi, Abdallah Bakari (My University, 2002)
To systematically evaluate the efficacy of double dose of sulfadoxine-pyremithamine (SP/SP) treatment in pregnancy in malaria endemic areas. Methods - The relevant articles were retrieved by a computerized search of Medline, Cochrane Review, Pub Med and Google with the following key words, sulfadoxine-pyrimethamine, intermittent, pregnancy, Quasi- experimental studies and Randomised Control Trials. Three reviewers identified only 2 papers meeting the inclusion criteria set for the study. Systematic quantitative review was performed.
A research report submitted to the Faculty of Health Sciences, University of the Witwatersrand, in fulfilment of the requirements for the degree of Master of Science in Medicine in Epidemiology and Biostatistics Johannesburg, 2002.
Keywords: Sulfadoxine; Pyrimethamine; Pregnancy; Pyrimethamine; Sulfadoxine; Pregnancy; Malaria